Fibrinolytic Activity and Platelet Function in Subjects with Obstructive Sleep Apnoea and a Patent Foramen Ovale: Is There an Option for Prevention of Ischaemic Stroke? - Reggiani, Monica; Karttunen, Vesa; Wartiovaara-Kautto, Ulla; Riutta, Asko; Uchiyama, Shinichiro; Hillbom, Matti (Stroke Research and Treatment, 2012)
Obstructive sleep apnoea (OSA) carries an increased risk of ischaemic stroke, but the underlying mechanism is not clear. As right-to-left shunting can occur through a patent foramen ovale (PFO) during periods of apnoea, we investigated nocturnal changes in fibrinolytic activity and platelet function in subjects who had OSA with or without PFO and in controls. We determined plasminogen activator inhibitor 1 (PAI-1) activity and antigen and platelet activation parameters. The severity of OSA was verified by polygraphy and PFO was detected by ear oximetry. We found a higher PAI-1 activity and antigen and a lower ratio of 2,3-dinor-PGF1α to 2,3-dinor-TXB2 in the subjects with OSA than in the controls. Linear regression analysis showed the apnoea-hypopnoea index (β-coefficient, 0.499; P=0.032) and PFO (β-coefficient, 0.594; P=0.015) to be associated independently with PAI-1 activity in the morning, while the increment in PAI-1:Ag from evening to morning was significantly associated with the presence of PFO (rs=0.563, P=0.002). Both OSA and PFO reduce fibrinolytic activity during nocturnal sleep. We hypothesize that subjects having both OSA and PFO may develop a more severe prothrombotic state during sleep than those having either OSA or PFO alone.